Optimizing Sports Training Lessons by Using the Led System for Beginner Basketball Groups - Adrian PAȘCAN; Cosmin MOCA (Cluj University Press, 2024)
Optimizing sports training lessons by using the LED system for beginner basketball groups. Objectives. This paper proposes the introduction into the training plan of the beginner basketball groups of some modern means, namely led systems for the development of reaction speed by making decisions to visual signals. The main purpose of this paper is to study the effects of this approach on the U13 players of the CSS Gheorgheni basketball team. Materials and methods: The subjects of the experiment were the athletes of the beginner basketball group born in 2010-2011, namely 16 girls. Initial tests were applied, then the players were subjected to specific training by applying some modern means, and at the end the same tests were applied again. Results: At the first test on execution speed, we notice that all the athletes managed to improve their results. From the point of view of mistakes, also in this test, we notice that almost all the participants in the experiment improved their performance, three of them managing not to make any mistakes. In the throwing test, they all improved their performance. In the combined test (changes of direction and throwing in the basket) 7 athletes finished the route without any mistakes, 7 girls improved their performance, and 2 girls had the same number of mistakes. Conclusions: based on the results obtained, we can say with certainty that by using exercises based on an LED system for the development of reaction speed by making decisions to visual signals throughout the season, the performance of the sportswomen under research has improved.  Optimizarea lecțiilor de antrenament sportive prin utilizarea sistemului led la grupele de baschet începători. Obiective. Această lucrare propune introducerea în planul de pregătire al grupelor de baschet începători a unor mijloace moderne și anume sisteme led pentru dezvoltarea vitezei de reacție prin luarea deciziilor la semnale vizuale. Scopul principal al acestei lucrări este de a studia efectele acestei abordări pe jucătoarele U13 ale echipei de baschet CSS Gheorgheni. Materiale si metode: Subiecții experimentului au fost sportivele grupei de baschet începători născute în anul 2010-2011, și anume 16 fete. S-au aplicat teste inițiale, apoi jucătoarele au fost supuse unor antrenamente specifice prin aplicarea unor mijloace moderne, iar la final s-au aplicat din nou aceleași teste. Rezultate: La primul test, la viteza de execuție, observăm că toate sportivele au reușit să își îmbunătățească rezultatele. Din punct de vedere al greșelilor, de asemenea, la acest test observăm că aproape toate participantele la experiment și-au îmbunătățit performanța, trei dintre ele reușind să nu facă nicio greșeală. La testul de aruncări, toate și-au îmbunătățit performanța. La testul combinat (schimbări de direcție și aruncare la coș) 7 sportive terminând traseul fără nicio greșeală, 7 fete și-au îmbunătățit performanța, iar 2 fete au avut același număr de greșeli. Concluzii: pe baza rezultatelor obținute, putem afirma cu certitudine că prin folosirea unor exerciții bazate pe un sistem LED pentru dezvoltarea vitezei de reacție prin luarea deciziilor la semnale vizuale pe tot parcursul sezonului, prestația sportivelor aflate în cercetare, s-a îmbunătățit. Cuvinte-cheie: mijloace moderne, sistem LED, viteza de reacție Article history: Received: 2024 February 13; Revised 2024 August 15; Accepted 2024 August 25; Available online: 2024 August 30; Available print: 2024 August 30